Application of Modified Slope Mass Rating (M-SMR) System in Ultrabasic Rock: A Case Study in Telupid, Sabah, Malaysia - Ismail Abd Rahim; Baba Musta; Riska Fadhila Abdullah (Indonesian Journal on Geoscience, 2023)
Modified Slope Mass Rating (M-SMR) was proposed as a geomechanically classification scheme for sedimentary Crocker Formation rock slope in the Kota Kinabalu area, but has never been applied in ultrabasic rock. Then, this study was conducted on ultrabasic rock cut slopes in Telupid, Sabah, Malaysia. This system was used to characterize and to propose preliminary rock cut slope design, slope stabilization, protection measures, and recommendation levels for slope re-investigation. The UCS test, Deere RQD method, a weighted average of discontinuity set spacing, weighted average and statistical mode, weighted average, and new approach of adjustment factor (NAAF) methods were used to evaluate the uniaxial compressive strength (UCS), RQD, discontinuity spacing, discontinuity condition, water flow and discontinuity orientation parameters, respectively. The result of this study shows that the M-SMR classes for the slopes are class III (moderate), IV (poor,) and class V (very poor). Recommended and highly recommended for slope re-investigation by well-trained, experienced, or expert engineering geologist/geotechnical engineer are for classes III, IV, and V, respectively. The recommendation for slope stabilization and protection measures are local trimming, surface drainage, horizontal drain, weep hole, systematic bolting, dowels, concrete detention or buttress, shotcrete, wire mesh or rope nets, and rock trap ditch.